Endomarketing: Satisfacción Laboral Desde La Perspectiva De Género Y Edad - Adriana Méndez Wong; Didier Varela Castro (European Scientific Journal, ESJ, 2018)
This paper focuses on analyzing the influence of the age and genre in the labor satisfaction of the sales professionals in the Southeastern region of Coahuila. The study makes use of a descriptive and quantitative approach. A questionnaire of 9 items was applied with Likert scale of 10 alternative answers. The study sample shows that 399 individuals were randomly selected. The findings of this study suggest that labor satisfaction is related to the genre, which shows that the samples of the men are more satisfied than the women. The recompensed salary is also a decisive factor on the feminine genre when they express their dissatisfaction with their job. In regards to the age, there are no statistically significant differences between those interviewed. In conclusion, the labor satisfaction is independent from the seller’s age.